Electrostatic Intraperitoneal Aerosol Delivery of Nanoparticles: Proof of Concept and Preclinical Validation. Issue 16 (16th June 2020) - Van de Sande, Leen; Rahimi‐Gorji, Mohammad; Giordano, Silvia; Davoli, Enrico; Matteo, Cristina; Detlefsen, Sönke; D'Herde, Katharina; Braet, Helena; Shariati, Molood; Remaut, Katrien; Xie, Feifan; Debbaut, Charlotte; et al.
Abstract: There is an increasing interest in intraperitoneal delivery of chemotherapy as an aerosol in patients with peritoneal metastasis. The currently used technology is hampered by inhomogenous drug delivery throughout the peritoneal cavity because of gravity, drag, and inertial impaction. Addition of an electrical force to aerosol particles, exerted by an electrostatic field, can improve spatial aerosol homogeneity and enhance tissue penetration. A computational fluid dynamics model shows that electrostatic precipitation (EP) results in a significantly improved aerosol distribution. Fluorescent nanoparticles (NPs) remain stable after nebulization in vitro, while EP significantly improves spatial homogeneity of NP distribution. Next, pressurized intraperitoneal chemotherapy with and without EP using NP albumin bound paclitaxel (Nab‐PTX) in a novel rat model is examined. EP does not worsen the effects of CO2 insufflation and intraperitoneal Nab‐PTX on mesothelial structural integrity or the severity of peritoneal inflammation. Importantly, EP significantly enhances tissue penetration of Nab‐PTX in the anatomical regions not facing the nozzle of the nebulizer. Also, the addition of EP leads to more homogenous peritoneal tissue concentrations of Nab‐PTX, in parallel with higher plasma concentrations. In conclusion, EP enhances spatial homogeneity and tissue uptake after intraperitoneal nebulization of anticancer NPs. Abstract : In theory, the combination of electrostatic precipitation with pressurized intraperitoneal chemotherapy (PIPAC), termed ePIPAC, can result in better tissue penetration of the aerosol. This theoretical advantage is confirmed in this project using a computational fluid dynamics model, an in vitro box model, and an in vivo rat model. Moreover, the peritoneal integrity is not affected by the applied electrostatic forces.